Cultivation of choice: new insights into farming practices at Neolithic lakeshore sites. (17th February 2016) - Styring, Amy; Maier, Ursula; Stephan, Elisabeth; Schlichtherle, Helmut; Bogaard, Amy
Abstract: Abstract : The high-quality organic preservation at Alpine lakeshore settlement sites allows us to go beyond simplistic reconstructions of farming in the Neolithic. The rich archaeological datasets from these sites may be further complemented by methods such as nitrogen isotope (δ 15 N) analysis of charred crop remains. At Hornstaad-Hörnle IA and Sipplingen, on the shore of Lake Constance in south-west Germany, this method has been used to provide a unique insight into strategies of cultivation such as manuring on both a spatial and temporal scale.